Polycystididae (Rhabditophora: Rhabdocoela: Kalyptorhynchia) from the Indian Ocean, with the description of twelve new species - Artois, Tom J.; Tessens, Bart S. (Zootaxa, 2008)
An overview of the Polycystididae from the Indian Ocean is presented, including the description of twelve new species. The taxonomical position of each of these species is discussed. Austrorhynchus kerguelensis n. sp., Paraustrorhynchus neleae n. sp., Paulodora ancora n. sp., P. contortoides n. sp., P. drepanophora n. sp., P. hamifer n. sp., P. porcellus n. sp., P. schockaerti n. sp., P. watsoni n. sp., Phonorhynchoides linguatus n. sp. and Polycystis elsae n. sp. can all be distinguished from their congeners on characteristics of the construction of the hard parts of the male system. The older records of Paulodora contorta (Schockaert & Karling, 1975) Artois & Schockaert, 1998 by Schockaert (1982) and Jouk & De Vocht (1989) are re-evaluated and the material is recognised as Paulodora drepanophora n. sp.. The subspecies P. felis asymmetrica Artois & Schockaert, 2001 is raised to the species level. Annalisella bermudensis Karling, 1978, Paraustrorhynchus elixus (Marcus, 1954) Karling & Schockaert, 1977 and Phonorhynchoides haegheni Artois & Schockaert, 2001 are recorded for the first time in the Indian Ocean. The new material of these species is discussed and compared with older descriptions. For Alcha evelinae Marcus, 1949, Cincturorhynchus karlingi Schockaert, 1982, Djeziraia pardii Schockaert, 1971 Gyratrix hermaphroditus Ehrenberg, 1831, Paulodora subcontorta (Schockaert, 1982) Artois & Schockaert, 1998 and Polycystis ali Schockaert, 1982 new localities are given, and newly collected material is discussed. The discussion of P. ali leads to the split of the species into P. ali Schockaert, 1982 from the African East Coast and Galapagos and P. californica n. sp. from California. For some of the species, new records outside the Indian Ocean are also mentioned.